AB0317 Do Cigarette Smoking Patients Have More Severe Early Rheumatoid Arthritis?. (9th June 2015) - Prodanovic, S.Z.; Radunovic, G.; Zlatanovic, M.; Simic-Pasalic, K.; Kadic, A.; Milic, V.; Sefik-Bukilica, M.; Damjanov, N.
Abstract : Background: Smoking in association with genetic factor can facilitate production of auto antibodies against citrullinated peptide and lead rheumatoid arthritis (RA) development (1). Objectives: To investigate the influence of cigarette smoking on severity of early rheumatoid arthritis. Methods: The 63 (85.7% female) early RA patients, mean age of 53.79±14.1 yrs. were enrolled in prospective observational study. All pts fulfilled EULAR/ACR 2010 criteria for diagnosis of early RA, had disease duration ≤12 months (in average 3.6 months) and have been without structural changes on radiography of hands and foot. Patients were treatment naïve for disease modifying anti-rheumatic drugs (DMARDs) and steroids. RA activity was assessed by the 28-joint disease activity score (DAS28-ESR) and bone erosions of hands and feet estimated by echosonography at the baseline, when early RA diagnosis was established and after 6 months of MTX (15 mg per week) therapy. Ultrasound examination was done by ESAOTE My Lab70 machine using 8-18 MHz linear probe according to OMERACT recommendations. The severity of smoking was estimated by pack/year: light (smoking ≤5 pack/yrs); moderate (5-20 pack/yrs) and heavy (≥20 pack/yrs), Anova statistical method was performed in data processing. Results: The total 33 (52.4%) early RA pts had never smoked, 11 (17.4%) pts. had stopped smoking at list 2 years before early RA onset. Nineteen (30.2%) pts. were current smokers. Three (4.8%) pts were a light-smokers, thirteen (20.6%) pts. were a moderate-smokers and three (4.8%) pts were a heavy smokers. Initially, there was no statistical difference between group of RA non-smokers, light-smokers, moderate or heavy-smokers pts regarding value of DAS28 score (mean value: 5.7; 6.5; 5.2; 6.1 respectively, p=0.387) and number of echo erosions (mean value: 2.4; 1.7; 2.3; 3.3 respectively, p=0.814). The group of moderate and heavy-smokers had statistically significant less decrease in DAS28 score than non-smokers and light-smokers (mean value: 0.9; 0.9; 1.7; 3.2 respectively, p<0.05) after 6 months of treatment. However, there was no statistically significant difference between heavy-smokers and moderate-smokers in comparison to non-smokers and light-smokers in increasing number of new echo erosions (mean value: 1.7; 0.2; 0.3; 1.0 respectively, p>0.05) after six months of therapy with MTX. Conclusions: After 6 months of MTX 15 mg/week treatment of sixty-three patients with early rheumatoid arthritis, non-smokers and light-smokers had significantly higher decrease of DAS28 score in comparison with group of moderate and heavy smokers. Number of new erosions observed by ultrasound was not significantly different between these groups. References: Klareskog L, Stolt P, Lundberg K et al. Smoking May Trigger HLA–DR (Shared Epitope)–Restricted Immune Reactionsto Autoantigens Modified by Citrullination, Arthritis & Rheumatism 2006; 54 (1): 38–46. Disclosure of Interest: None declared